If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(s + -4) = -85 Reorder the terms: 10(-4 + s) = -85 (-4 * 10 + s * 10) = -85 (-40 + 10s) = -85 Solving -40 + 10s = -85 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + 10s = -85 + 40 Combine like terms: -40 + 40 = 0 0 + 10s = -85 + 40 10s = -85 + 40 Combine like terms: -85 + 40 = -45 10s = -45 Divide each side by '10'. s = -4.5 Simplifying s = -4.5
| 2m-8=10+18 | | 3x+1y=392 | | 14x-9=11y | | 900000000000000000000000000000000+423523542546224624246426264462264264642426264426565374676585798966975685362431432134245436356457764575976980=x | | k-3(5)=12(5) | | 7-3x=x+3x | | X^2+11X+19=X-6 | | 7r+2=(5r-4) | | 8(3-5m)= | | 2(3x+3)+6(x-4)= | | 8x+17=-5(3-8x) | | 8.1-1.5x=-6.9 | | 3x^3+x^2-2=0 | | 2*5+x= | | -4(5y-6)-y=-3(y-4) | | 42y+4=16 | | 42y+4=17 | | 6.2m+3-1.9=-5.72 | | 8y=y+6+3 | | -(-(-k))-(-2)(-2+k)=-k-(4k+3) | | -2(6y-5)-y=-4(y-3) | | 15x+3=28+10x | | (5v+7)(5-v)=0 | | 8x+9=6x*15 | | -18-x=12 | | 0.63m=-3 | | -4(6y-8)-y=-4(y-3) | | -[3x+(3x+9)]=9-(4x+3) | | X-2+x-3+123=180 | | 2y+12=21 | | 44=-4v | | 3(x+1)+4=22 |